Heterodox theories of inflation - Özden, Oktay (Taylor and Francis, 2025)
The present chapter delves into heterodox theories of inflation. The chapter consists of two main sections. The first one examines the evolution of Post Keynesian, institutionalist, and Marxian theories on inflation. Post Keynesians argue that pricing power and distributional conflicts are crucial factors influencing prices, although the cost base structure also plays a significant role in inflation. Institutionalists propose the concept of administered prices, where sellers adjust prices based on new information. Marxians consider profit, capital, and power as the driving forces behind capitalism. These forces exert both pulling and resisting pressures on market prices. While these schools of thought interact with one another, they approach the issue from different angles and emphasize different aspects. Thus, the section also highlights their points of convergence and divergence. The subsequent section investigates recent inflation and its impact on income and wealth distribution. The COVID-19 pandemic has sparked debates about the causes of current inflation and has drawn scholars’ attention toward these heterodox approaches. Consequently, this section elucidates the drivers of current inflation and evaluates the implications of these heterodox perspectives. © 2026 selection and editorial matter, Tae-Hee Jo, Lynne Chester, and Carlo D’Ippoliti; individual chapters, the contributors.
Keywords: Inflation; 'Current; Base Structure; Cost Basis; Driving Forces; Income Distribution; Market Price; Power; Price-Based; Wealth Distributions; Costs